1990
DOI: 10.1056/nejm199006213222502
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetically Determined Polymorphic Drug Metabolism in the Beta-Blockade Produced by Propafenone

Abstract: Propranolol and the sodium-channel-blocking antiarrhythmic agent propafenone share structural features. Although propafenone's beta-blocking actions are readily demonstrable in vitro, clinically significant beta-blockade occurs inconsistently in vivo. In this study, we tested the hypothesis that genetically determined variations in the biotransformation of propafenone to its 5-hydroxy metabolite account for variations in the drug's beta-blocking action. We assessed beta-blockade by measuring the reduction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…CYP2D6 status is generally thought to matter little for antiarrhythmic effect (Siddoway et al, 1987;Labbe et al, 2000), although some studies have suggested greater efficacy in those with reduced CYP2D6 activity (Jazwinska-Tamawska et al, 2001;Cai et al, 2002). PMs may be predisposed to more central nervous system adverse effects (76 versus 14% in EMs) (Siddoway et al, 1987) and greater ␤-blockade (Lee et al, 1990;Morike and Roden, 1994), although the latter result has been contradicted (Labbe et al, 2000). There is a case report of toxicity (dizziness and bradycardia) in a PM (Morike et al, 1995).…”
Section: Antipsychoticsmentioning
confidence: 96%
See 1 more Smart Citation
“…CYP2D6 status is generally thought to matter little for antiarrhythmic effect (Siddoway et al, 1987;Labbe et al, 2000), although some studies have suggested greater efficacy in those with reduced CYP2D6 activity (Jazwinska-Tamawska et al, 2001;Cai et al, 2002). PMs may be predisposed to more central nervous system adverse effects (76 versus 14% in EMs) (Siddoway et al, 1987) and greater ␤-blockade (Lee et al, 1990;Morike and Roden, 1994), although the latter result has been contradicted (Labbe et al, 2000). There is a case report of toxicity (dizziness and bradycardia) in a PM (Morike et al, 1995).…”
Section: Antipsychoticsmentioning
confidence: 96%
“…The propafenone/ 5-hydroxypropafenone ratio correlates with the debrisoquine metabolic ratio . PMs have 3-to 7-fold higher propafenone AUCs at steady state than EMs and produce very low or negligible concentrations of 5-hydroxypropafenone (Siddoway et al, 1987;Kroemer et al, 1989a;Lee et al, 1990;Dilger et al, 1999;Labbe et al, 2000). CYP2D6 status is generally thought to matter little for antiarrhythmic effect (Siddoway et al, 1987;Labbe et al, 2000), although some studies have suggested greater efficacy in those with reduced CYP2D6 activity (Jazwinska-Tamawska et al, 2001;Cai et al, 2002).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…This is generally not clinically significant. The parent molecule does have β-blocking activity, whereas the metabolite does not, and so adverse effects due to β-blockade are more common with the deficient CYP2D6 activity (Lee et al 1990). Flecainide is also a CYP2D6 substrate but is also excreted unchanged by the kidneys.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…& The antiarrhythmic propafenone is eliminated by metabolism through the cytochrome P450 CYP2D6, and in individuals with deficient CYP2D6 activity, parent drug accumulates and side effects, including bradycardia (likely due to beta blockade) are common [12,13]. CYP2D6 activity is absent in 7% of Caucasians and African -Americans (''poor metabolizers'') because they are homozygous for loss of function alleles, dozens of which have now been described (http://www.imm.ki.se/ CYPalleles/).…”
Section: Mechanisms Underlying Variability In Drug Actionmentioning
confidence: 99%